Transforming East African ICT Sector by Creating a Business Engine for SMEs : SMEs and the East Africa ICT Sector - Ewing, Javier; Okolloh, Ory; Rawlings, Lauren (World Bank, Washington, DC, 2017)
For the purposes of this project, the East African countries included in the study were Kenya, Rwanda, Tanzania, and Uganda. The focus for this project was Small and Medium-sized Enterprises (SMEs) as for-profit or nonprofit organizations with less than 50 employees and not exceeding USD 1,000,000 in annual revenues/turnover. The main output of this project was a proposed program of interventions to drive transformational change. To succeed in this ambitious endeavor, the project articulated clear objectives and designed a blueprint for implementation including levels of resourcing, budget and monitoring metrics. Over the course of the project the team conducted brief surveys with over 90 entrepreneurs, over 50 percent of who had 3-10 years of experience in the Information and Communication Technology (ICT) sector and primarily worked at companies with 5 employees or less.